An Examination of the use of Data and Analytics in Talent Management in MNCs - Hietanen, Niina (My University, 2019)
Talent management has for many years received considerable attention in human resource management (Alziari 2017). The role of analytics is also becoming more important in decision making and performance in many organizations (Liberatore, Pollack-Johnson & Clain 2017). However, there is a lack of research on analytics, and organizations also find it difficult to understand how to utilize analytics for their advantage in practice. (Kiron, Ferguson & Prentice 2013; Douthitt & Mondore 2014: Gobble 2017.) This study focuses on examining how data and analytics are and can be used in talent management. In addition, the possible future opportunities and challenges in the field of data and analytics and talent management are discussed. The empirical part of this study was conducted by using qualitative research method and the data was collected by conducting semi-structured interviews with human resource professionals form five different Finnish multinational companies. The findings of the study indicate that the use of data and analytics in the organizations is different from the level of the use as well as from the purpose of the use. In addition, relatively lot attention is paid on performance data and the use of it. However, there is strong interest of develop the use of data and analytics to support employee engagement and training.
Keywords: Strategic human resource management; Talent Management; Talent Data; Talent Analytics; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|